Propuesta de mejora de control de inventario de equipos de protección personal en un terminal portuario - Gómez Arreaga, Carolyn Narcisa (2023)
This project is oriented in the proper control of the inventory of a warehouse of personal protection equipment in which the industrial safety area of the port terminal is responsible for its management, so it is of utmost importance to have the necessary equipment, keep records of equipment delivered for each partner and keep the warehouse stocked for good management. To carry out this project, several objectives were proposed, through the analysis of the situation with all the learning acquired in the university career, to set these objectives, all the problems that happened in this winery were evaluated and with the appropriate actions, propose solutions to avoid mismanagement of inventory that could lead to more serious issues such as not providing equipment for port terminal workers. Before arriving at solutions to the problem, an analysis was made of the possible causes, to get to the root cause through the Ishikawa or fish thorn diagram that allowed us to make a visual representation and categorize from the minor cause to the most influential in depth, determine the effect and prevent the problem as time goes by being greater, such as the loss of a life due to failure to deliver protections.